Development and calibration data for the Healthcare Access Item Bank: a new computer adaptive test for persons with type 2 diabetes mellitus. - Carlozzi, Noelle E.; Kallen, Michael A.; Troost, Jonathan P.; Bragg, Alexa; Martin-Howard, Jessica; De La Cruz, Barbara; Miner, Jennifer A.; Moldovan, Ioana; Jack, Brian W.; Mitchell, Suzanne (Quality of Life Research, 2023)
Purpose: The purpose of this study was to develop a new measure to evaluate the ability to receive medical services when needed among persons with type 2 diabetes mellitus.Methods: The Healthcare Access measure was developed using data from 225 persons with type 2 diabetes mellitus who completed an item pool comprised of 54 questions pertaining to their experience accessing healthcare services.Results: Exploratory and confirmatory factor analyses supported the retention of 45 items. In addition, a constrained graded response model (GRM), as well as analyses that examined item misfit and differential item functioning (investigated for age, sex, education, race, and socioeconomic status), supported the retention of 44 items in the final item bank. Expert review and GRM item calibration products were used to inform the selection of a 6-item static short form and to program the Healthcare Access computer adaptive test (CAT). Preliminary data supported the reliability (i.e., internal consistency and test-retest reliability) and validity (i.e., convergent, discriminant, and known-groups) of the new measure.Conclusions: The new Healthcare Access item bank can be used to examine the experiences that persons with type 2 diabetes mellitus have with healthcare access, to better target treatment improvements and mitigate disparities; it will be available as a part of the Neuro-Qol measurement system through healthmeasures.net and the PROMIS Application Programmable Interface (API) in early 2023.